The COVID-19 Pandemic Between Bio-Ethics, Bio-Law and Bio-Politics: A Case Study on The Italian Experience of The DuPre Commission - Testoni, Ines (ETHICS IN PROGRESS, 2022)
The aim of this qualitative study was to consider the question of whether the Italian political management of the pandemic respected the European bio-ethical and bio-juridical approaches in light of the principles of autonomy, dignity, integrity and vulnerability. As no specific consolidated literature exists on the subject, the Italian situation was taken into consideration, specifically the work of a spontaneous commission (DuPre) that collected the reflections of academics and researchers interested in discussing political decisions for the management of the emergency, which was the coronavirus disease (COVID-19) pandemic. The analysis took into account the contributions of scholars during two conferences (without proceedings), which were transcribed and examined. From the texts processed with a thematic analysis, three main themes emerged: ‘pandemic as a state of exception, sovereignty and crisis of democracy’, ‘the value of doubt and refutation’ and ‘elimination of informed consent between persuasion and blackmail’. In this paper, the final bio-political considerations on the European approach and the management of the COVID-19 pandemic in Italy are presented.